2012
DOI: 10.1371/journal.pone.0030875
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of the Viral Microbiome in Patients with Severe Lower Respiratory Tract Infections, Using Metagenomic Sequencing

Abstract: The human respiratory tract is heavily exposed to microorganisms. Viral respiratory tract pathogens, like RSV, influenza and rhinoviruses cause major morbidity and mortality from respiratory tract disease. Furthermore, as viruses have limited means of transmission, viruses that cause pathogenicity in other tissues may be transmitted through the respiratory tract. It is therefore important to chart the human virome in this compartment. We have studied nasopharyngeal aspirate samples submitted to the Karolinska … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
120
1
4

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 162 publications
(130 citation statements)
references
References 39 publications
5
120
1
4
Order By: Relevance
“…Although there are viruses of Eukarya inhabiting these sites (Victoria et al, 2009;Foulongne et al, 2012;Lysholm et al, 2012), the majority of the viruses that have been identified in these habitats are bacteriophage (Breitbart et al, 2008;Willner et al, 2009). As has been demonstrated in other environments (Breitbart et al, 2002;Angly et al, 2006), viral communities in the human body are diverse and generally composed of numerous different genotypes.…”
Section: Introductionmentioning
confidence: 98%
“…Although there are viruses of Eukarya inhabiting these sites (Victoria et al, 2009;Foulongne et al, 2012;Lysholm et al, 2012), the majority of the viruses that have been identified in these habitats are bacteriophage (Breitbart et al, 2008;Willner et al, 2009). As has been demonstrated in other environments (Breitbart et al, 2002;Angly et al, 2006), viral communities in the human body are diverse and generally composed of numerous different genotypes.…”
Section: Introductionmentioning
confidence: 98%
“…Postsequencing processing is applied to raw sequence data to perform quality control (QC), filter reads for contamination, map reads toward relevant genomes, assemble genomes (or partial genomes), and perform homology searches and taxonomic/phylogenetic studies. 29,64,65 This is shown in Figure 2 as a flowchart of methodologies and implementation of methodologies for analysis. Quality of datasets for metagenomic analysis consists of several parts.…”
Section: Bioinformatics and Processing Of Datamentioning
confidence: 99%
“…Genotyping of RSV group A into (GA2, GA5 and GA7) by means of a novel method based on PCR, FRET (Fluorescence Resonance Energy Transmission) detection and two -dimensional melting curve analysis was carried out by Rafiefard et al [15]. In recent years, viral metagenomic sequencing has become an established method both for finding novel viruses and for detecting the presence of known viruses in new environments [16]. There was no vaccine currently approved for paramyxovirus-induced respiratory diseases in humans, Le Bayon et al [17] reviewed the immunogenicity (increase in neutralizing antibody titres) and the protection conferred by the most promising recombinant vectored vaccines against human respiratory syncytial virus, human metapneumovirus and human parainfluenza viruses types 1 to 3, which are significant causes of upper and lower tract respiratory diseases.…”
mentioning
confidence: 99%